Islamic values in ethical principles of social work - Nur Saadah Mohamad Aun,; Zaenal Abidin,; Nur Madihah Ili Idrus, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Allah s.w.t. commands every human to help one another with righteousness and piety and forbids helping one another with sin and hostility. Similarly, in the profession of social work, which emphasizes the concept of helping and doing good deeds. As a profession, social workers also have the function of solving social problems based on values by fulfilling human needs and aspirations. Therefore, a study was conducted to understand social work and its connection with religious values, especially Islam. A qualitative study using in-depth interview techniques was conducted with four social workers at a government agency. The results of the study indicate that there are religious elements, namely Islamic values, in the principles of social work ethics. One of the Islamic values that is often associated with Islam is the giving of zakat, which is one of the Pillars of Islam. The obligation to pay zakat applies to those who can give to the poor as prescribed in Islam. This is in line with the social work principles of the National Association of Social Workers (NASW), which aim to provide services to clients with the goal of helping them and identifying their problems. Based on this study, Islamic values are closely related to the social work profession, which adheres to principles and ethics in social work.